Different Approaches to the Development of Online Learning in Higher Education - Kornilov, Iurii V. (2020)
The relevance of the study is substantiated by the intensive transition of the educational process to the digital environment. In this context, methods and principles of teaching, which are necessary to meet the society needs in modern education, are changing and developing. The authors reveal the issue of the global economy transformation, focusing on digital environments (digitalization). It is highlighted that digitalization contributes to the increasing demand for personnel and the necessity to improve the education system. The analysis of the theoretical features of online education is conducted, methods of its organization are identified, and modern requirements for teaching in higher education are determined. The key concepts that are the basis for the study are clarified. Approaches to the classification of online course formats and their other essential features are generalized. The authors introduce the classification of online learning in terms of time (synchronous, asynchronous) and the classification according to the degree of the educational process integration with online technologies. Additionally, the character of participants’ interaction (web support, blended learning, and fully online learning) is generalized. A review of online courses models by the format of participants’ interaction is carried out (model of online repository courses, xMOOC, cMOOC, hMOOC, ahMOOC, SPOC). The processes of online learning implementation, including e-learning and distance learning technologies in higher education have been revealed. The experience of the development of the first online courses at M. K. Ammosov North-Eastern Federal University is described. As a part of the study, the main approaches to the development of online learning in higher education are identified. The authors of the study focus on the work of the advanced training courses for the academic staff as the opportunity for professional competencies development in the context of online education.